(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Acceptability of smoked, boiled and barbecued catfish by consumers are dependent on numerous factors. Consumer acceptability study allows industries to tailor the supply towards the preference of consumers so that market could be optimized for their turn-over and profits. This study investigated consumer acceptability of boiled, smoked and barbecued African catfish in Awka, Anambra state, Nigeria. A total of 70 questionnaires were administered adopting multi-stage techniques to elicit information from the respondents about socio-economic characteristics of respondents, determinants of consumer preference, forms of fish consumed, The obtained data were subjected to descriptive and inferential statistical analysis. The results showed that majority of the respondents in the study preferred barbecued catfish (47.15) irrespective of their socio-economic profile when compared to smoked catfish (40.0%) and boiled catfish (12.9%).It is recommended that efforts from government, private sectors and fish folks should be put into subsidizing the production inputs of catfish as this will in turn reduce price of catfish and encourage increased regular consumption of catfish.